From “It Has Stopped Our Lives” to “Spending More Time Together Has Strengthened Bonds”: The Varied Experiences of Australian Families During COVID-19 - Evans, Subhadra; Mikocka-Walus, Antonina; Klas, Anna; Olive, Lisa; Sciberras, Emma; Karantzas, Gery; Westrupp, Elizabeth M. (Frontiers in Psychology, 2020)
The present study uses a qualitative approach to understand the impact of COVID-19 on family life. Australian parents of children aged 0–18 years were recruited via social media between April 8 and April 28, 2020, when Australians were experiencing social distancing/isolation measures for the first time. As part of a larger survey, participants were asked to respond via an open-ended question about how COVID-19 had impacted their family. A total of 2,130 parents were included and represented a diverse range of family backgrounds. Inductive template thematic analysis was used to understand patterns of meaning across the texts. Six themes were derived from the data, including “Boredom, depression and suicide: A spectrum of emotion,” “Families are missing the things that keep them healthy,” “Changing family relationships: The push pull of intimacy,” “The unprecedented demands of parenthood,” “The unequal burden of COVID-19,” and “Holding on to positivity.” Overall, the findings demonstrated a breadth of responses. Messages around loss and challenge were predominant, with many families reporting mental health difficulties and strained family relationships. However, not all families were negatively impacted by the restrictions, with some families reporting positive benefits and meaning, including opportunities for strengthening relationships, finding new hobbies, and developing positive characteristics such as appreciation, gratitude, and tolerance.